Video Transmission using Combined Scalability Video Coding over MIMO-OFDM Systems - Kalvein Rantelobo; Hendro Lami; Wirawan Wirawan (Institute of Advanced Engineering and Science, 2016)
The needs of efficient bandwidth utilization and method to handle bandwidth fluctuation condition of wireless channel have become fundamental problems in video transmission. This research proposed Combined Scalable Video Coding (CSVC) that refers to Joint Scalable Video Model (JSVM), i.e. development of video coding H.264/AVC by exploiting scalable combination method using Medium Grain Scalability (MGS) on wireless channel of MIMO-OFDM (Multiple Input Multiple Output – Orthogonal Frequency Division Multiplexing) technology. The research shows that the scalable combination method can be implemented on the scenario for wireless transmission on multicast network. Experimental results show that the delivered quality is close to the alternative traditional simulcast delivery mechanism in MIMO-OFDM systems.